Get ready for A & P / Lori K Garrett - Garrett, Lori K
"This hands-on book gets you up to speed with important study skills, math skills, anatomical terminology, basics of the human body, chemistry, and cell biology ... Each chapter includes a pre-test, guided explanations, helpful activities, quizzes and end-of-chapter cumulative test."